2015
DOI: 10.1186/s13071-015-1269-4
|View full text |Cite
|
Sign up to set email alerts
|

First report of naturally infected Sergentomyia minuta with Leishmania major in Tunisia

Abstract: BackgroundMany sand fly species are implicated in the transmission cycle of Leishmania parasites around the world. Incriminating new sand flies species, as vectors of Leishmania is crucial to understanding the parasite–vector transmission cycle in different areas in Tunisia and surrounding countries.FindingsSeventy-four unfed females belonging to the genera Sergentomyia and Phlebotomus were collected in South Tunisia between June and November 2014, using sticky papers. PCR-RFLP (Restriction Fragment Length Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 11 publications
4
20
0
1
Order By: Relevance
“…S. minuta is recorded in arid region of Tunisia with an annual precipitation between 88 and 157mm (53), also in Portugal with an annual precipitation equal to 730mm (64). In the present study, it prefers regions with an annual precipitation (Bio 12) between: 50-1100mm, and precipitation seasonality (Bio 15) between: 30-100mm (Supporting Information S1).…”
Section: Discussionsupporting
confidence: 52%
“…S. minuta is recorded in arid region of Tunisia with an annual precipitation between 88 and 157mm (53), also in Portugal with an annual precipitation equal to 730mm (64). In the present study, it prefers regions with an annual precipitation (Bio 12) between: 50-1100mm, and precipitation seasonality (Bio 15) between: 30-100mm (Supporting Information S1).…”
Section: Discussionsupporting
confidence: 52%
“…Nevertheless, some recent investigations in Tunisia and Portugal have reported the detection of L. major and L. infantum DNA in Se. minuta [ 48 , 52 , 53 ] suggesting its potential role in the transmission of mammal-infecting Leishmania . Also, Senghor et al and Berdjane-Brouk et al suggested that Sergentomyia species could be involved in the transmission of L. major and L. infantum in Africa [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these efforts should be pursued and completed by abundance studies [69]. Regarding Sergentomyia species, very little is known, nevertheless these species deserve more attention due to their possible association with TOSV transmission [60] and their putative role in Leishmania transmission [70][71][72][73].…”
Section: Sandflies As Tosv Vectorsmentioning
confidence: 99%